Integrated Analysis and Finding Reveal Anti-Liver Cancer Targets and Mechanisms of Pachyman (Poria cocos Polysaccharides) - Li Qin; Dongning Huang; Jian Huang; Fuhui Qin; Haixin Huang (Frontiers Media S.A., 2021)
This bioinformatics study aimed to characterize and certify crucial anti-cancer targets, functional processes, and molecular mechanisms of Pachyman in treating hepatocellular carcinoma (HCC) by using pharmacology network and molecular docking analyses, by experimental validation. The crucial anti-HCC targets of Pachyman, including ALB, VEGFA, TNF, CASP3, SRC, EGF, CXCR4, STAT3, HRAS, HSP90AA1, MMP9, BCL2L1, FGF2, and PTPRC, were identified. In addition, the correlative networks of all crucial biotargets of Pachyman in treating HCC were created accordingly. Functionally, these crucial genes were correlated using angiogenesis and neoplastic metastasis of HCC. Interestingly, the molecular docking findings indicated that ALB and VEGFA in HCC might be potent pharmacological targets of Pachyman. In experimental validation, the clinical samples of HCC showed reduced ALB protein expression and increased VEGFA protein level. Following Pachyman treatments in vitro, the intracellular level of ALB protein was elevated, whereas the cellular content of VEGFA protein was downregulated. Taken together, current bioinformatics findings based on pharmacology network and molecular docking analyses elucidate the detailed molecular targets and signaling mechanisms of Pachyman in treating HCC. Interestingly, validated biotargets of ALB and VEGFA may be main potential biomarkers for detecting HCC medically.